143 Catastrophising cognitions in patients with psychogenic non-epileptic seizures compared to patients with epilepsy. Issue 6 (27th May 2022) - Whitfield, Andrew; Walsh, Sean; Levita, Liat; Reuber, Markus
Abstract : A growing body of evidence suggests more catastrophising cognitions are present in patients with psychogenic non-epileptic seizures (pwPNES) compared to patients with epilepsy (PWE). However, the perseverative aspect of catastrophic thinking including repetitive negative thinking (RNT) has had little attention. In this study pwPNES (n=26) and PWE (n=29) completed self-reported questionnaires including Perseverative Thinking Questionnaire to assess levels of RNT and a modified version of the Safety Behaviors and Catastrophizing Scale to assess catastrophising of seizures. Participants also completed the PHQ-9 and GAD-7 to provide measures of anxiety and depression. Patients with PNES reported significantly higher levels of RNT, catastrophising of seizures, and depression and anxiety than patients with epilepsy. Additionally, the effect of RNT was independent to effects of all other factors in its contribution to PNES suggesting it would serve as a good target for psychological therapy. ajwhitfield1878@gmail.com